PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM PEMBELAJARAN BAHASA INGGRIS DI KELAS VI UPT SD INPRES PARANG - Fachrul Achsan Saputra; Dewi Mitra Maulidya; Nurazmi; Wahyuni Antasari (STKIP Subang, 2024)
This study aims to determine the improvement in student engagement in learning English among students of Class VI.A at UPT SD Inpres Parang, who were taught using the Teams Games Tournament method. The type of research used is Classroom Action Research (CAR), with data collection conducted using observation sheets. The subjects of the research are students of Class VI at UPT SD Inpres Parang, Makassar City Regency. The population of this study includes all sixth-grade students at UPT SD Inpres Parang for the 2024/2025 academic year. The research sample was taken from one class, VI.A, consisting of 16 students. The study results show that using the Teams Games Tournament learning model can increase student engagement in learning English in Class VI at UPT SD Inpres Parang. This can be seen from the initial observation, which showed a score of 54.98%. In Cycle 1, this increased to 65.83%. Then, in Cycle 2, it reached 78.76%, and in Cycle 3, it rose to 89.07%.